Análisis del control de inventario y su incidencia en la liquidez de la Empresa Ecuamoldes - Rodríguez Sailema, Ruddy Michelle (2023)
The industrial companies that are dedicated to the commercialization of inputs and accessories have an extensive range of products, which are differentiated by their functions, categories and quality, which is why they tend to have shortcomings in the control of stocks, shortages or surpluses of commodity; in many occasions they can harm the financial statements by showing the assets of the inventory and can degrade over time; Therefore, it is extremely important to keep track of the merchandise that enters and leaves the premises since it would help to improve efficiency, reduce costs and increase the liquidity of the company. The present research work in the company Ecuamoldes, is intended to solve the problem that arises, the need to obtain adequate inventory control has been generated. A mixed approach methodology was carried out in which it was collected through descriptive research through the application of data collection techniques such as survey and interview, documentary analysis allowing to know the reality of the entity in the development of inventory control. , obtaining information from the primary sources as well as the incidence in the liquidity of the company was verified. Where the need to design a manual of processes and procedures for inventory control was evidenced in which each function is assigned, the detail of processes and the main procedures for the personnel, with this the best performance of the company is guaranteed, improving control in inventories guaranteeing liquidity in the company.